1983
DOI: 10.1177/002383098302600201
|View full text |Cite
|
Sign up to set email alerts
|

The Acquisition of Communicative Intentions in Infants Eight to Fifteen Months of Age

Abstract: The acquisition of a set of nonverbal intentionally communicative behaviors is described for six preverbal infants followed longitudinally between eight and 15 months of age. The infants were observed at monthly intervals as they interacted with their mothers in a free play situation. There was a statistically significant trend for the set of communicative intentions to emerge in the following sequence: Protesting, Request for Action, Request for Object, Comment on Action, Comment on Object, and Answering. Ges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
56
0
2

Year Published

1990
1990
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(66 citation statements)
references
References 7 publications
6
56
0
2
Order By: Relevance
“…She found that, in many cases, calling and requesting were differentiable on the basis of nonsegmental vocal patterns. Carpenter, Mastergeorge & Coggins (1983) found that by o;io, infants' vocal patterns reliably correlate with the pragmatic functions of requesting and protesting. While we did not systematically manipulate social situations, Jenny was recorded in a variety of interactive modes, and we were rarely able to hear any affect in her vocalizations.…”
Section: Pragmatic Use Of the Voicementioning
confidence: 93%
“…She found that, in many cases, calling and requesting were differentiable on the basis of nonsegmental vocal patterns. Carpenter, Mastergeorge & Coggins (1983) found that by o;io, infants' vocal patterns reliably correlate with the pragmatic functions of requesting and protesting. While we did not systematically manipulate social situations, Jenny was recorded in a variety of interactive modes, and we were rarely able to hear any affect in her vocalizations.…”
Section: Pragmatic Use Of the Voicementioning
confidence: 93%
“…An intentional communicative act is defined as a gesture, vocalization or word that is directed at someone to convey a message (Cress et al 2013). These behaviours develop long before meaningful speech (Carpenter et al 1983), and they do so in a particular order in typically developing children: (i) protesting, (ii) request for action, (iii) request for object, (iv) comment on action, (v) comment on object and (vi) answering (Carpenter et al 1983). Children with developmental disabilities may not follow the same progression as typically developing children when learning these actions (Rescorla & Merrin 1998).…”
Section: Development Of Pre-speech and Pre-language Behavioursmentioning
confidence: 99%
“…As McNeill (1992) noted, in human languages gesture and speech modalities are coordinated not only at the temporal and phonological levels (i.e., the most prominent part of the gesture is typically aligned with the most prominent part of speech), but also at the semantic and pragmatic levels (i.e., the two components can share similar semantic functions). Infants begin to use simultaneous gesture-speech combinations intentionally near the end of the first year of life, a few months after the onset of canonical babbling and typically preceding the beginning of the one-word production stage (Butcher & Goldin-Meadow, 2000;Carpenter, Mastergeorge & Coggins, 1983;Esteve-Gibert & Prieto, 2014). The presence of these combined, multimodal communicative behaviors have been taken as an indicator of intentional communication, representing a step further on the way toward linguistic communication (Bates, Camaioni, & Volterra, 1975;Bates, Benigni, Bretherton, Camaioni, & Volterra, 1979;Wetherby & Prizant, 1989).…”
Section: Introductionmentioning
confidence: 99%